2016
DOI: 10.1007/s00221-016-4741-2
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns of limb coordination in infant rolling

Abstract: Infants must perform dynamic whole-body movements to initiate rolling, a key motor skill. However, little is known regarding limb coordination and postural control in infant rolling. To address this lack of knowledge, we examined movement patterns and limb coordination during rolling in younger infants (aged 5-7 months) that had just begun to roll and in older infants (aged 8-10 months) with greater rolling experience. Due to anticipated difficulty in obtaining measurements over the second half of the rolling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Rolling over in early human development is a dynamic whole-body movement with multiple body parts and interactions with the floor (Shirley 1931;Gesell and Thompson 1934;McGraw 1941;Bayley 1993). Most previous studies on rolling over described movements mainly from the viewpoint of kinematics (Richter et al 1989;VanSant 1990;Yamamoto 2011;Kobayashi et al 2016). For example, a study on adult rolling from the supine to the lying position showed various combined kinematic patterns of the body parts, including the upper limb, lower limb, head, and trunk (Richter et al 1989).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rolling over in early human development is a dynamic whole-body movement with multiple body parts and interactions with the floor (Shirley 1931;Gesell and Thompson 1934;McGraw 1941;Bayley 1993). Most previous studies on rolling over described movements mainly from the viewpoint of kinematics (Richter et al 1989;VanSant 1990;Yamamoto 2011;Kobayashi et al 2016). For example, a study on adult rolling from the supine to the lying position showed various combined kinematic patterns of the body parts, including the upper limb, lower limb, head, and trunk (Richter et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…intensively studied (Adolph et al 2018), understanding of rolling over has not been deepened in the last decade. Kobayashi et al (2016) used a three-dimensional (3-D) motion analysis system to measure the movements of several body parts in infants and classified kinematic patterns and their developmental changes. Thus, previous studies showed the kinematic characteristics of rolling over.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is indicated by numerous literatures that the migration effect of alternately training of two-side limbs shall be apparently higher than the training effect of merely one-side limb (Raza et al, 2016). Some articles also refer to the empirical research by taking two-side migration as a teaching method (Milovanovic et al, 2015), and point out that two-side migration has facilitation to sports skills of student, development of coordination, sport injury prevention and reduction and learning interest cultivation (Kobayashi et al, 2016). Two-side migration of sports skills is a part of the whole brain teaching content, and it has positive effect on teaching promotion in the sports teaching practice (Gooijers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%